2016
DOI: 10.1002/stc.1835
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pounding mitigation and stress waves in highway bridges with shape memory alloy pseudo-rubber shock-absorbing devices

Abstract: Summary Seismic‐induced pounding between adjacent structures that are insufficiently separated can cause significant structural damage, even collapse, during severe earthquakes. This paper presents an experimental and numerical investigation into mitigating pounding on highway bridges using novel shape memory alloy pseudo‐rubber shock‐absorbing devices (SMAPR‐SADs). The mechanical properties and a theoretical model of SMAPR‐SADs are briefly introduced and investigated. Next, a series of shaking table tests on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The impact force and corresponding impulsive contact stress were difficult to obtain; however, it is important to further study the dynamic properties and damage analysis in the SC system. In addition, it is noted that the classical contact-pounding element model (Figure 3) is widely employed in impact problems [18][19][20]23,24 in adjacent bridge structures (including frontal and oblique impacts) and can accurately capture the time-history results of impact and damping forces. Several theoretical contact-pounding models have been investigated and selected in the study of pounding process, such as the liner model, the Kelvin model, and the Hertz model, etc.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…The impact force and corresponding impulsive contact stress were difficult to obtain; however, it is important to further study the dynamic properties and damage analysis in the SC system. In addition, it is noted that the classical contact-pounding element model (Figure 3) is widely employed in impact problems [18][19][20]23,24 in adjacent bridge structures (including frontal and oblique impacts) and can accurately capture the time-history results of impact and damping forces. Several theoretical contact-pounding models have been investigated and selected in the study of pounding process, such as the liner model, the Kelvin model, and the Hertz model, etc.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, those modified values could be applied to the other analyses in the same structure. The authors have performed many shaking table tests of pounding problems 23,24 and the results indicated that the parameters of Hertz model calculated by the equations still could provide a reasonable reference value. As shown in Figure 9, the lateral displacement response of the FEM and proposed theoretical model agree well with the test results.…”
Section: Verification Of the Proposed Dynamical Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has high elasticity, large restorable deformation, and a self-recovery ability. All the SMAPR specimens in this study were fabricated at the Metallic Pseudo-Rubber Technique Research Centre of the Harbin Institute of Technology (Jiang et al, 2001;Li et al, 2011Li et al, , 2016. The SMAPR specimens comprised martensite NiTi (50 at.% Ni) SMA wires with a diameter of 0.2 mm, and the martensitic SMA wires used in this study were fabricated from austenitic NiTi wires at room temperature.…”
Section: Smaprmentioning
confidence: 99%
“…In 2015, Singh and Satpute pointed out that energy dissipation and seismic reduction technology based on traditional design can greatly improve the seismic, wind and seismic capacity of buildings and structures, effectively reduce the response and damage of wind and earthquake to structures, and improve the seismic capacity and seismic performance of structures [3]. In 2016, Li et al proposed a method for seismic strengthening of four-to six-storey frame structures with friction dampers, which are located in the 8-degree earthquake intensity zone and site II [4]. In 2015, Pu et al used friction dampers to analyze and calculate the seismic strengthening of frame structures with six stories, which effectively improved the seismic performance of structures.…”
Section: Literature Reviewmentioning
confidence: 99%